PROBLEM PRAKTIK KHURÛJ BAGI ANGGOTA JAMA`AH TABLIGH DI MADURA - Faiqoh Bahjah Lailatus Siyami; Siti Musawwamah (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2015)
Khurûj is one of the teachings which is tightly attached to Jama`ah Tabligh that ordered all its followers to go out of the district/area to spread amr al-ma`rûf nahy al-munkar in a certain time. The main problem is when the khurûj obligation is faced to Family obligation. Those obligations can create problems when the member of the Jama`ah Tabligh cannot make the obligation to the family and the khurûj obligation balance. One of the examples is the divorce of the member of the Jama`ah Tabligh. The reason of the divorce is because the lack of living cost when the husband did the khurûj. To fulfill it, the wife gets debt from other people and she cannot pay it off. Doing the khurûj is an activity of Jama`ah Tabligh, where a member will be stated as a legal member when he has joined the khurûj. Khurûj concept in its application is devided into 3 phases. The First is 3 days in a month; the second is 40 days in a year, and the last is 4 months in a lifetime. But the theory of the counting is using unknown and unclear base either from Al-Qur’an and al-Sunnah or any other methods of dakwah that applied by Rasulullah. While Jama`ah Tabligh uses Saying from Al-Qur’an as theoretical foundation about khurûj, that is the word “ukhrijat” containing in QS. Ali Imran (3): 110